2020
DOI: 10.1111/cfs.12785
|View full text |Cite
|
Sign up to set email alerts
|

Care leaver needs and accessibility: Findings from the first large‐scale project in Switzerland

Abstract: Leaving out-of-home care is a challenging situation not only for young people leaving care but also for the child welfare system. However, systematic and multiorganizational transitional programmes are often lacking. This study investigated Switzerland's first large-scale care leaver programme and analysed associations between care leavers' needs and contactability in a sample of 459 care leavers. A first

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…However, some authors discuss whether this link is due to the persons having the better ‘qualifications’ at adolescence being more likely to receive aftercare or to the aftercare itself having a positive impact on the young adult outcomes (Valset, 2018). Jarczok et al (2020) examined how aftercare related to well‐being and found that care leavers accepting the aftercare programme rated their quality of life lower than those reporting no need for support. In our study, a substantial proportion of the respondents (13.3% of the boys and 7.5% of the girls) did not know whether they had received/were receiving aftercare.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors discuss whether this link is due to the persons having the better ‘qualifications’ at adolescence being more likely to receive aftercare or to the aftercare itself having a positive impact on the young adult outcomes (Valset, 2018). Jarczok et al (2020) examined how aftercare related to well‐being and found that care leavers accepting the aftercare programme rated their quality of life lower than those reporting no need for support. In our study, a substantial proportion of the respondents (13.3% of the boys and 7.5% of the girls) did not know whether they had received/were receiving aftercare.…”
Section: Discussionmentioning
confidence: 99%
“…Care-leavers clearly recommend that extended care should be offered to all young adults living in foster or residential care (e.g., Werner et al, 2019). A study about an aftercare programme shows that care-leavers could profit from coaching sessions, but also that many of the young people could not be reached by the programme (Jarczok, Knecht Krüger, Mitrovic, Gérard, & Jud, 2020). Until now, there is no research on the effects of staying in care beyond age 18.…”
Section: Romaniamentioning
confidence: 99%
“…Die Konferenz für Kindesund Erwachsenenschutz (KOKES) sowie die Konferenz der kantonalen Sozialdirektorinnen und -direktoren (SODK) haben gemeinsam Empfeh- lungen für einvernehmliche sowie angeordnete Platzierungen in Heimund Familienpflege erarbeitet, welche zukünftig als Qualitätsstandards gelten sollen (Wider et al, 2021) (Rein, 2018;ders., 2020) thematisiert (Eberitzsch, 2021). Obwohl diese Thematik im internationalen Vergleich in der Schweiz lange Zeit vernachlässigt wurde (Jarczok et al, 2021), hat sie in den letzten Jahren in fachlichen Diskursen in der Schweiz zugenommen. Dies äussert sich beispielsweise an einer zunehmenden Zahl an Fachartikeln, Fachtagungen (Rein, 2018) oder an aktuell laufenden Längsschnittstudien 3 .…”
Section: Ausserfamiliäre Platzierungen In Der Schweiz: Situation Heuteunclassified